The pros and cons of remaining in a 401(k) plan after retirement - Mitchell, Olivia S.; Reilly, Catherine; Turner, John A. (Financial Services Review, 2023)
This paper examines whether retirees would benefit from staying in their companies’ 401(k) plans after retirement, versus rolling their savings over to Individual Retirement Accounts (IRAs). Our focus is on individuals having low or moderate levels of financial literacy. We conclude that many such retirees would likely find it financially rewarding to retain their assets in their 401(k) plans. While IRAs currently offer a wider range of advice or distribution options compared with 401(k) plans, we close by pointing to legislative and technological developments that may produce better outcomes, more retirement confidence, and greater security for retirees.